Community Gender Norms Change as a Part of a Multilevel Approach to Sexual Health Among Married Women in Mumbai, India - Schensul, Stephen L. (Am J Community Psychol, 2015)
Inequitable gender norms in societies and communities negatively contribute to women’s sexual and reproductive health. While the need for change in gender norms is well recognized, the task is highly challenging in terms of intervention design, implementation and assessment of impact. This paper describes a methodology for identification of gender norms, the design of community level intervention, community participation and the assessment of intervention impact in a low income, predominately Muslim community of 600,000 people in Mumbai, India. Formative research focused on in-depth interviews with women, men and couples yielding gender normative statements and assessment of community resources to facilitate change. A Gender Equity Scale (GES) based on this formative research was developed and administered annually for a three-year period to random, cross-sectional samples in the intervention and control communities, and to community based, non-governmental organizations (NGO) staff and Imams (religious leaders) in the intervention community. NGO staff disseminated gender oriented messages to their female constituency through their regular outreach activities and through special events and festivals in the community. Imams disseminated gender messages through lectures on social issues for men attending Friday prayers. The results showed that the NGO staff and Imams, assumed more gender equitable attitudes across time. The intervention was associated with a significant improvement in attitudes towards gender equity in the intervention relative to the control community. Men showed a dramatic change in more positive gender attitudes, while women lagged behind in their GES scores. The meaning of these results are explored and the implications assessed for the generalizability of the methodology for other countries, cultures and communities.